A simple and rapid direct injection method for the determination of glyphosate and AMPA in environmental water samples - Okada, Elena; Coggan, Timothy; Anumol, Tarun; Clarke, Bradley; Allison, Graeme (Springer Verlag, 2020)
Glyphosate is currently the most widely used herbicide in the world, yet screening of environmental waters for this chemical is limited by the need for specialized derivatization and measurement methods that can be tedious and time-consuming. In this work, we present a novel method for the detection and quantification at trace levels of glyphosate and aminomethylphosphonic acid (AMPA) in environmental water samples. The detection and quantification of the analytes was performed by liquid chromatography (LC) coupled with tandem mass spectrometry (MS/MS). Chromatographic separation was achieved with an ion-exchange column and a pH-gradient elution of a solution of ammonium hydroxide and ammonium acetate. The limit of detection for glyphosate and AMPA was 0.25 μg L-1 and the limit of quantification was 0.5 μg L-1with a 20-μL injection. The method was used to investigate the levels of glyphosate and AMPA in surface water samples from the Yarra River catchment area and urban constructed stormwater wetlands. The results indicate that at the time of sampling, no glyphosate or AMPA was present in the samples from the Yarra River catchment area (n = 10). However, glyphosate was detected above the limit of quantification in 33% of the wetland samples (n = 12), with concentrations ranging from 1.95 to 2.96 μg L-1. Similarly, AMPA was quantified in 83% of the wetland samples, with concentrations ranging from 0.55 to 2.42 μg L-1. To our knowledge, this is the first report of a pH-gradient LC–MS/MS method for glyphosate and AMPA analysis at ultratrace levels, with minimal sample processing, avoiding costly, time-consuming derivatization and preconcentration steps.